EVALUATION OF WALNUT SHELL ABRASIVE SANDPAPER (FUDMA JOURNAL OF SCIENCES, 2021)
This study is focused on development of an eco-friendly abrasive sandpaper using walnut shell (WS) with the binding effect of epoxy resin on WS, iron oxide and silica, calcium carbonate (CaCO3) and pulverized graphite. The method of mixing and mould compression using a hydraulic press matrix composite with five varying composition was used. The compositions were made by varying  the weight of WS, epoxy resin with that of iron oxide and silica, calcium carbonate and pulverized graphite were left constant expressed in percentage weight The abrasive properties investigated were density, compressive strength and wear resistance and water and oil absorption rate. The results reveals obtained that the density, wear resistance rate and compressive strength of the tested composition decreases with increasing WS content despite the fact the rate water absorption increases with increasing WS. The result of obtained reveals that WS can be utilized in the production of abrasive sandpaper
Keywords: Wear rate, absorption, Abrasive sandpaper, Epoxy and Silica sand